KOMPOSISI KIMIA MINYAK ATSIRI DAUN AKWAY (Makara Journal of Science, 2011)
Chemical Composition of Essential Oil from Akway. Akway (Drimys piperita Hook f.) is a woody, evergreen and aromatic plan that was a member of winteraceae. This plant is used by Sougb tribe lived in Sururey village, District of Manokwari, to heal malaria and to enhance the vitality of body. The objectives of this research were to know the yield of essential oil using water distillation of leaves and its chemical composition using gas chromatography and mass spectroscopy (GC-MS). The results indicated that the yield of leaves essential oil by using water distillation was 0.2%. The essential oil composed by 49 compounds categorized by terpene and its derivatives 83.67%, derivatives of benzene 4.08% and alifatic compounds 8.16%